A Nationwide Analysis Evaluating the Safety of Using Acellular Dermal Matrix with Tissue Expander-Based Breast Reconstruction - Luo, Jessica; Moss, Whitney D.; Pires, Giovanna R.; Rhemtulla, Irfan A.; Rosales, Megan; Stoddard, Gregory J.; Agarwal, Jayant P.; Kwok, Alvin C. (Archives of Plastic Surgery, 2022)
Background In March 2021, the United States Food and Drug Administration (FDA) safety communication cautioned against the use of acellular dermal matrix (ADM) products in breast reconstruction and reiterated that the FDA does not approve ADM use in breast surgery. This study aims to assess the safety of ADM use in breast reconstruction.Methods Women who underwent ADM and non-ADM assisted tissue expander (TE)-based breast reconstruction were identified using the National Surgical Quality Improvement Program database (2012–2019). Trends of ADM use over time, and 30-day outcomes of surgical site infection (SSI), dehiscence, and unplanned reoperation were assessed.Results Of the 49,049 TE-based breast reconstructive cases, 42.4% were ADM assisted and 57.6% non-ADM assisted. From 2012 to 2019, the use of ADM increased from 26.1 to 55.6% (relative risk [RR] =1.10; p < 0.01). Higher rates of SSI (3.9 vs. 3.4%; p = 0.003) and reoperation (7.4 vs. 6.0%; p < 0.001) were seen in the ADM cohort. There was no significant difference seen in dehiscence rates (0.7 vs. 0.7%; p = 0.73). The most common reoperation within 30 days for the ADM group (17.6%) was removal of TE without insertion of implant (current procedural terminology: 11,971). ADM-assisted breast reconstruction was associated with increased relative risk of SSI by 10% (RR = 1.10, confidence interval [CI]: 1.01–1.21; p = 0.03) and reoperation by 15% (RR = 1.15, CI: 1.08–1.23; p < 0.001).Conclusions ADM-assisted breast reconstruction more than doubled from 2012 to 2019. There are statistically higher complication rates of SSI (0.5%) and reoperation (1.4%) with ADM use in TE-based breast reconstruction, suggesting that reconstruction without ADM is safe when comparing immediate postoperative outcomes.
Keywords: tissue expander; breast reconstruction; outcomes; acellular dermal matrix